Role of common salt in the treatment of umbilical cord granuloma - Sharma, Chandra Madhur; Aggarwal, Bindu; Chaudhary, Piyush (International Journal of Contemporary Pediatrics, 2020)
Background: Umbilical granuloma is an overgrowth of granulation tissue following the separation of umbilical cord. Treatment options for this common entity are limited and have side effects such as chemical burns. In this study, we want to highlight the salt application method for treatment of infants with umbilical granuloma. Methods: Thirty six infants were enrolled in present study after institutional ethics committee approval and consent from the parents. After thoroughly explaining the method to all mothers, they are advised to apply a pinch of salt on granuloma twice a day for 3 days .The area of application was cleaned, and common table salt was carefully applied over the lesion. The granuloma was then occluded with surgical adhesive tape for 30 minutes. Cases were followed up after 3 days for assessment of improvement. Results: All thirty six cases responded well to this approach with complete resolution of lesions after 3 days. Small clot like shrunken tissue was found at the site of granuloma, which was easily scraped off during gentle cleansing. No major complication or recurrence was noted in follow-up. Conclusions: The use of common salt in treating umbilical granuloma is simple, cost-effective, curative, and safe. It is easily administered and can be performed by parents at home.